LEARNING DISCIPLINE RELATIONSHIP WITH LEARNING OUTCOMES PRACTICE BUILDING CONSTRUCTION CLASS X TGB SMKN 5 PADANG TP 2015/2016. - 1914-1929 Charles Hermanto Sibarani (CIVED, 2016)
This study aims to reveal the relationship disciplined student learning to the learning outcomes of building construction practices class X TGB student of SMKN 5 Padang TP 2015/2016. Research type used is correlational. The population in this research is class X TGB SMKN 5 Padang TP 2015/2016 academic year as many as 29 peoples. The research sample as many as 29 students were taken using total sampling technique. The file used is primary and secondary file. File analysis techniques used are : (1) descriptive analysis, (2) testing requirements analysis, which consists of normality test, homogeneity and linearity test to prove that the distribution of the data comes from samples normally distributed, homogeneous and linear, and (3) hypothesis testing. The analysis showed that there is a significant relationship between the discipline of learning the results of class X TGB student of SMKN 5 Padang TP 2015/2016 with 95% confidence level. It can be seen from the Sig (2 - tailed) 0.048 < Alpha (0.05) and the results obtained contribute only showed a value of 13.69 %. Based on the acquisition of these test results, it can be concluded that there is a significant relationship between the discipline of learning the results of class X TGB student of SMKN 5 Padang TP 2015/2016 .   Keywords : Relationship, Discipline learning, Learning Outcomes